EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY (TSTS) DAN THINK-PAIR-SHARE (TPS) PADA MATERI PERSAMAAN DAN PERTIDAKSAMAAN LINEAR SATU VARIABEL DITINJAU DARI KARAKTERISTIK CARA BERPIKIR SISWA KELAS VII SMP NEGERI DI KABUPATEN PACITAN - Kusuma, Fitriana Anggar; Budiyono, Budiyono; Subanti, Sri (Jurnal Pembelajaran Matematika, 2014)
Abstract: The objective of research was to find out: (1) which learning models provided the better mathematics learning achievement, Two Stay Two Stray (TSTS), Think Pair Share (TPS) or direct learning, (2) which category of thinking pattern characteristics provided the better mathematics learning achievement, concrete sequential (SK), abstract sequential (SA), random concrete (AK) or abstract concrete (AA), (3) in each learning model, which category provided the better mathematics learning achievement SK, SA, AK or AA thinking patterns, and (4) in each category of student thinking pattern characteristics, which learning model provided the better mathematics learning achievement, TSTS, TPS or direct learning models. This study was a quasi-experimental research with a 3x4 factorial design. The population of research was all of the VII graders of Junior High Schools in Pacitan Regency. The sampling technique used was stratified cluster random sampling. The sample of research consisted of 237 students 81 students for experimental class 1 and 77 students for experimental class 2 and 79 students for control class. Considering the hypothesis test, the following conclusions could be drawn. (1) The learning using TSTS model provided the better mathematics learning achievement than the one using TPS, and the TSTS and TPS models provided learning achievement as good as the direct learning model did in one-variable equation and disequation material. (2) The learning achievement of the students with SK type of thinking pattern characteristics was better than that of those with SA and AK types, but that of those with SK type was as good as that of those with AA type, that of those with SA type as good as that of those with AK, and that of those with AA was better than that of those with SA and AK types of thinking pattern characteristics. (3) In TSTS, TPS and direct learning models, the mathematics learning achievement of the students with SK type was better than that of those with SA and AK types, but that of those with SK was as good as that of those with AA, that of those with SA was as same as that of those with AK, and that of those with AA was better than that of those with SA and AK types of thinking pattern characteristics. (4) In the thinking pattern characteristics of SK, SA, AA, and AK types, the TSTS learning model provided the better mathematics learning achievement than the TPS model and the TSTS and TPS provided better learning achievement than direct learning model in one-variable linear equation and disequation material.Keywords: Two Stay Two Stray (TSTS), Think-Pair-Share (TPS), Student’s Thinking Pattern Characteristics.